Operationalizing irrigation water charges in Sub-Saharan Africa: a case study from the Central Rift Valley, Ethiopia - Hagos, Fitsum; Ahmed, J.T.; Haileslassie, Amare; Seid, Abdulkarim (IWA Publishing, 2022)
Fixing and implementing water charges in the irrigation sector is considered an important task for recovering operation and maintenance costs and promoting the efficient use of water. This study aims at developing an implementation strategy for water charges in the Central Rift Valley, Ethiopia. The study sets the agenda for this strategy by explaining why promoting the concept of fixing irrigation charges is necessary. Then it develops a conceptual framework, draws key lessons from global experiences, explores whether the new pricing policy is well aligned with national water policies and the roles and responsibilities of various actors and stakeholders involved, and identifies the factors for the successful implementation of this strategy. The study is mainly qualitative in nature, based on a review of the literature and consultations of key stakeholders. The study results call for clearly defining the key objectives of the policy, political commitment, and community participation, re-examining the role of institutions, capacity building, and establishing a multistakeholder platform. Basin-level implementation of this policy requires piloting and maintaining policy dynamics through adaptive management. The results provide generic lessons for other basins within Ethiopia and for sub-Saharan Africa (SSA).